Contribution of financial market development in competitiveness growth - Mohammad W. Alomari; Zyad Marashdeh; Ala G. Bashayreh (Cogent Economics & Finance, 2019)
The study aims at re-examining the relationship between financial market development and economic development in the context of competitiveness of developed and higher income countries. Methodology/approach: The study employs generalized least square (GLS) regression model to analyze the panel data of 21 higher income countries over the period (2009-2017). Further, the study checked the robustness of the results by introduces a lagged dependent variable in the regression models by employing the generalized methods of moments (GMM) for Dynamic Panel analysis. Findings: Results reveal that four independent variables: Financial market development (FMDG), trade openness (OPNG), Labor market efficiency (LMEG), and Technological readiness (TRG), were positive and significant, which indicates the existence of relationship from those variables to competitiveness in the context of growth. while one of the independent variables is Market size (MSG) was positive but insignificant. Moreover, the results from the GMM estimator remain robust in terms of directions and significance levels and confirm the robustness of the findings. Originality: This paper represents a significant contribution especially for the higher income countries that can help them in designing the policies and strategies in order to improve their performance and competitiveness by financial market development besides other competitiveness sources.
Keywords: O16; O47; 330; competitiveness; financial markets development; economic growth; higher income countries